Reports of recent years on physiotherapy and the health of children - Jaworski, Piotr (Journal of Education, Health and Sport, 2021)
The physiotherapy process in children is specific and requires much more patience and understanding than in adults. Working with a child is not only related to the physiotherapy of a small patient, but also in a very good cooperation between the parent-physiotherapist. The paper presents selected issues of children's therapy in the light of research papers published in renowned scientific journals dealing with medical issues.